Ancient mitogenomics elucidates diversity of extinct West Indian tortoises - Christian Kehlmaier (Nature Portfolio, 2021)
Abstract We present 10 nearly complete mitochondrial genomes of the extinct tortoise Chelonoidis alburyorum from the Bahamas. While our samples represent morphologically distinct populations from six islands, their genetic divergences were shallow and resembled those among Galápagos tortoises. Our molecular clock estimates revealed that divergence among Bahamian tortoises began ~ 1.5 mya, whereas divergence among the Galápagos tortoises (C. niger complex) began ~ 2 mya. The inter-island divergences of tortoises from within the Bahamas and within the Galápagos Islands are much younger (0.09–0.59 mya, and 0.08–1.43 mya, respectively) than the genetic differentiation between any other congeneric pair of tortoise species. The shallow mitochondrial divergences of the two radiations on the Bahamas and the Galápagos Islands suggest that each archipelago sustained only one species of tortoise, and that the taxa currently regarded as distinct species in the Galápagos should be returned to subspecies status. The extinct tortoises from the Bahamas have two well-supported clades: the first includes one sample from Great Abaco and two from Crooked Island; the second clade includes tortoises from Great Abaco, Eleuthera, Crooked Island, Mayaguana, Middle Caicos, and Grand Turk. Tortoises belonging to both clades on Great Abaco and Crooked Island suggest late Holocene inter-island transport by prehistoric humans.